Mini-invasive revascularization operations in the complex treatment of neuroischemic and ischemic forms of diabetic foot syndrome (Bangladesh Journal of Medical Science, 2021)
Objective: Diabetic foot syndrome is the most dramatic complication of diabetes mellitus. The treatment success is impossible without improving blood circulation and the elimination of hemodynamic disorders in the affected limb.The study aim was to evaluate mini-invasive revascularization operations effectiveness on the lower limbs peripheral arteries in neuro-ischemic and ischemic diabetic foot syndrome forms.Materials and methods: The study enrolled 104 patients with purulent-necrotic complications of diabetic foot syndrome. 54 (51.9%) patients underwent stenting and balloon angioplasty (the main group). The comparison group included 50 (48.1%) patients, undergoing indirect revascularization surgeries in complex treatment.Results and discussion:After endovascular interventions, the API index increased by 47.6% (p